Pengaruh Net Working Capital Dan Profitabilitas Terhadap Nilai Perusahaan dengan Growth Opportunity Sebagai Variabel Intervening pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Wan Ridha Khairuna; Kustoro Budiarta (Universitas Methodist Indonesia, 2025)
This study aims to analyze the effect of Net Working Capital (NWC) and Profitability on Firm Value with Growth Opportunity as an intervening variable in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The research method used is a quantitative approach with secondary data analysis obtained from the financial statements of companies listed on the IDX. The analysis technique used in this study is path analysis with the Partial Least Square (PLS-SEM) approach. The results of the study show that Net Working Capital (NWC) has a significant effect on Growth Opportunity, but does not directly affect Firm Value. Profitability has a positive and significant effect on Growth Opportunity and Firm Value, indicating that companies with high profitability tend to have better firm value. In addition, Growth Opportunity acts as an intervening variable that mediates the effect of Net Working Capital and Profitability on Firm Value. The implications of this study indicate that companies in the transportation and logistics sector need to pay attention to working capital management and increase profitability in order to maximize firm value. Increasing growth opportunities through the right investment strategy can help increase the company's attractiveness in the eyes of investors and strengthen the company's financial stability.